Image-based orange (Citrus Reticulata and Citrus Reticulata Blanco) sweetness measurement by ResNet50 - Pornpanomchai, Chomtip (Asia-Pacific Journal of Science and Technology, 2025)
This research aims to develop a computer system that can evaluate an orange’s sweetness from a single image. The system is called orange sweetness measurement system (OSMS). The system was used on 120 orange images taken from 20 video clips, each lasting 60 s. The system extracted 400 video frames as images from each video clip. It used 200 images to train the system and the remainder to validate it. The system employed ResNet50 to train, validate, and recognize orange images. It had eight procedures, 1) collecting oranges, 2) making orange video clips, 3) squeezing orange juice, 4) measuring orange sweetness with a refractometer, 5) training the dataset, 6) imaging to evaluate orange sweetness, 7) recognize an orange image, and 8) display recognition results and sweetness values. The precision rate of the system is 99.35%, with an average access time of 1.5248 s/image. Based on the experimental results, orange sweetness can be measured using only a single image.